Archival contingencies: institutional afterlives of an antipodal library. Issue 10 (2nd October 2020) - Balkin, Sarah
ABSTRACT: Ernest Scott (1867–1939), an early history professor at the University of Melbourne, left thirteen thousand books to the university library after his death. This article considers Scott's books, many of which contain subject-specific newspaper clippings and annotations, as an archive in a state of institutional flux. Scott's books and clippings give us insight into what historian of the modern research university William Clark calls 'the material practices of academics'. I examine such practices as they intersect with the kinds of institutional inertia that 'new institutionalists' from the fields of sociology and political economy see as scripting human actions and encouraging stasis. The institutional afterlives of Scott's library focus our attention on mundane, low-stakes, and obsolescent research practices even as they work against the idea of archives as rational and disenchanted. By examining two of Scott's clipping-filled books, both collections of essays by late nineteenth-century theatre critics, I ask what we can learn from considering provenance, media, and modes of storage and access as part of a collection's content.